Incidental diagnosis of combined deficiency of vitamin C and D in a child admitted with bronchiolitis (Northern International Medical College Journal, 2020)
Several cases from developing countries has been reported either on isolated vitamin C or isolated vitamin D deficiency in the recent past. Though nutritional vitamin C deficiency is rare but recently there is re-emergence of vitamin D deficiency found in developed countries. Combined deficiency of vitamin C and D found in the same patient is very rare both in developed and developing countries. Our patient was admitted in Ad Din Women’s Medical College Hospital, Dhaka with bronchiolitis. She had a history of cough and cold for 5 days. She had fever and respiratory difficulty for the last 2 days. On physical examination, she had low grade fever, fast breathing, chest in drawing. She had also widening of the wrist and ankle joints but her parents were unaware of these changes. They thought these could be a normal phenomenon. We suspect Rickets on physical examination findings. The baby was very much irritable and we thought that it was due to cough, cold and difficult breathing (bronchiolitis). Combined vitamin C and D deficiency was an incidental finding in this case. Her X ray of wrist joints, lower limb including knee and ankle joints showed the features of combined deficiency of vitamin C and D.Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 435-437